Traffic noise pollution at residential area - Izzaty Mohd Isa, Ilyani; Zafflina Mohd Zaki, Zaizatul; Kassim, Jalina (International Journal of Engineering and Technology, 2018)
Most people are unaware of noise pollution occurring around them due to the characteristic of the pollution itself. This pollution is not visible to peopleâ€™s sense and affects people based on their sound level acceptance. Since people who have high sound level acceptance are familiar with noise, thus noise pollution will not directly annoy them. This study was conducted to determine the traffic noise level at Seksyen 7, Shah Alam and its correlation with traffic volume. Since noise level will affect people in terms of annoyance and lead to health effect, the study area were chosen at intersections nearby residential area. The data of traffic noise level and traffic volume were collected representing weekday and weekend for each intersection. Three (3) data collection session were conducted for each day, which is in the morning (0730-0830), in the afternoon (1230-1330) and in the evening (1700-1800). The collected data were then being analysed and compared with the standard limit set by the Department of Environment Malaysia (DOE) to check whether the noise level at the study area comply with the limit recommended.Â Â